A three‐gene leukaemic stem cell signature score is robustly prognostic in chronic myelomonocytic leukaemia. (6th February 2023) - Wang, Yu‐Hung; Yao, Chi‐Yuan; Lin, Chien‐Chin; Gurashi, Kristian; Amaral, Fabio M. R.; Bossenbroek, Hasse; Jerez, Andres; Somervaille, Tim C. P.; Binder, Moritz; Patnaik, Mrinal M.; Hou, Hsin‐An; Chou, Wen‐Chien; et al.
Summary: Leukaemic stem cell (LSC) gene expression has recently been linked to prognosis in patients with acute myeloid leukaemia (17‐gene LSC score, LSC‐17) and myelodysplastic syndromes. Although chronic myelomonocytic leukaemia (CMML) is regarded as a stem cell disorder, the clinical and biological impact of LSCs on CMML patients remains elusive. Making use of multiple independent validation cohorts, we here describe a concise three‐gene expression signature (LSC‐3, derived from the LSC‐17 score) as an independent and robust prognostic factor for leukaemia‐free and overall survival in CMML. We propose that LSC‐3 could be used to supplement existing risk stratification systems, to improve prognostic performance and guide management decisions.